2020
DOI: 10.3390/ijms21134638
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of the Midbrain Dopaminergic Neuronal Identity

Abstract: The mesodiencephalic dopaminergic (mdDA) group of neurons comprises molecularly distinct subgroups, of which the substantia nigra (SN) and ventral tegmental area (VTA) are the best known, due to the selective degeneration of the SN during Parkinson’s disease. However, although significant research has been conducted on the molecular build-up of these subsets, much is still unknown about how these subsets develop and which factors are involved in this process. In this review, we aim to describe the life of an m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 127 publications
0
29
0
Order By: Relevance
“…In the last few decades, mechanisms involving the developmental process of DA neurons have been elaborately described. The establishment of DA neurons is orchestrated by intrinsic transcriptional factors and environmental cues with a number of stages: neuronal induction, regional patterning/specification, and DA induction [23,30,43,45,47,48]. Chemicals S/C/D [19], morphogens S/F8/F2 [24,25,49] and transcription-factor cocktail MLN [16,17,19,33], which have been reported in a series of studies, promoted the sequential developmental stages of DA generation (Figure 7).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the last few decades, mechanisms involving the developmental process of DA neurons have been elaborately described. The establishment of DA neurons is orchestrated by intrinsic transcriptional factors and environmental cues with a number of stages: neuronal induction, regional patterning/specification, and DA induction [23,30,43,45,47,48]. Chemicals S/C/D [19], morphogens S/F8/F2 [24,25,49] and transcription-factor cocktail MLN [16,17,19,33], which have been reported in a series of studies, promoted the sequential developmental stages of DA generation (Figure 7).…”
Section: Discussionmentioning
confidence: 87%
“…Over the last few decades, a variety of in vitro induction paradigm was established for the induction into DA neurons, including multiple molecules affecting both the intrinsic transcriptional regulation and the extrinsic microenvironment state [21][22][23][24]. For example, the morphogens such as sonic hedgehog (SHH), fibroblast growth factor 8 (FGF8), and basic fibroblast growth factor (FGF2) represent the floor plate-based strategy for the induction into DA neurons [25,26] and are essential for the generation of stem cell-derived DA neurons [24,25,27]; meanwhile, these morphogens also were supplemented in induction paradigm of cell fate conversion of somatic cells to increase the efficiency of DA neurons [19].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, clinical and neurophysiological evidence revealed that dopaminergic dysfunction is also implicated in AD pathophysiology [21][22][23][24][25][26][27][28][29]. In a transgenic model of AD, Nobili et al [30] demonstrated a progressive degeneration of neurons from the ventral tegmental area (VTA) (i.e., a dopaminergic-rich structure located in the midbrain) [31], which correlated behaviourally with reward and memory functions [30,32]. Notably, the mesocortico-limbic system, which is strictly involved in reward [33,35], as well as in executive and memory functions [30,36,37] stems from dopamine neurons located in the VTA midbrain region.…”
Section: Introductionmentioning
confidence: 99%
“…Of these subsets, the neuroanatomically distinct substantia nigra (SNc) and ventral tegmental area (VTA) are best known, mainly due to the selective degeneration of the SNc during Parkinson’s disease (PD) [ 9 ]. The specification of the different subsets in the mdDA system is dependent on a unique set of transcription factors and signaling cascades during development [ 4 , 5 , 6 , 7 , 8 , 10 ], although knowledge of the factors that are important during subset specification is currently insufficient.…”
Section: Introductionmentioning
confidence: 99%